1987
DOI: 10.1901/jeab.1987.48-117
|View full text |Cite
|
Sign up to set email alerts
|

Devaluation of Stimuli Contingent on Choice: Evidence for Conditioned Reinforcement

Abstract: Pigeons were presented a concurrent-chains schedule of reinforcement that had terminal links of equal duration. The initial links of the schedule were periodically interrupted by 15-s periods during which an extinction schedule was in effect. The extinction periods were presented on either a responsecontingent or a noncontingent basis. Relative response rate for the left alternative decreased when the extinction periods were accompanied by the left terminal-link stimulus. Relative response rate for the right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Studies have shown that if the rate of primary reinforcement is equal for two alternatives, but one alternative delivers conditioned reinforcers at a higher rate, subjects will exhibit a preference for this alternative (Dunn, Williams, & Royalty, 1987;Williams & Dunn, 1991). However, rate of conditioned reinforcement is a difficult concept to define in a discretetrial procedure, and the studies demonstrating the effects of the rate of conditioned reinforcement have been conducted using concurrent-chain procedures.…”
Section: Choice With Probabilistic Reinforcersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that if the rate of primary reinforcement is equal for two alternatives, but one alternative delivers conditioned reinforcers at a higher rate, subjects will exhibit a preference for this alternative (Dunn, Williams, & Royalty, 1987;Williams & Dunn, 1991). However, rate of conditioned reinforcement is a difficult concept to define in a discretetrial procedure, and the studies demonstrating the effects of the rate of conditioned reinforcement have been conducted using concurrent-chain procedures.…”
Section: Choice With Probabilistic Reinforcersmentioning
confidence: 99%
“…This approach can also explain the results of studies that found a preference for whichever alternative delivered a higher rate of conditioned reinforcers, when the rate of primary reinforcement was equal for the two alternatives (Dunn et al, 1987;Williams & Dunn, 1991). For instance, Williams and Dunn used a concurrent-chain procedure with VI schedules as the initial links and FI 20-sec schedules as the terminal links.…”
Section: Comparison With Other Models Of Delayed Reinforcementmentioning
confidence: 99%
“…As a result, it was impossible to determine whether the controlling variable was the response-reinforcer delay or the delay from the onset ofthe stimulus. It is now clear that it is the latter, because variations in the correlation of the stimulus with food (e.g., by providing separate extinction periods for the stimulus), while leaving constant the response-reinforcer delays, strongly affect preference (Dunn, Williams, & Royalty, 1987). There remains, however, the question as to why the value of a stimulus should be predicted only by the time to reinforcement associated with its onset, instead of by the rates of reinforcement occurring throughout the entire stimulus duration.…”
Section: Examples Ofunresolved Issuesmentioning
confidence: 99%
“…These stimuli affect choice as conditioned reinforcers because they predict reinforcer delivery and can acquire conditioned value [26]. For example, in one study [27], pigeons chose between concurrent variable-interval (VI) 120-s initial links leading to illumination of a center key light (terminal link stimulus) that co-occurred with a fixed-interval (FI) 20-s terminal link ending in food delivery.…”
Section: Introductionmentioning
confidence: 99%